2018
DOI: 10.5755/j01.sace.21.4.19501
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Cultural Landscapes of Central Yakutia for the Development of Scientific Tourism

Abstract: In this article authors analyse natural and cultural landscapes for scientific tourism. Central Yakutia with the unique permafrost landscapes is a rich and large territory of sites of interest for the development of "scientific tourism" for explorers, researchers or eco-natural-tourists. There are three types of scientific tourism relevant for Central Yakutia: the aim of which is scientific research; the aim of which is practical training and education of students of educational institutions; the aim of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For instance, Buzinde et al advocate for the potential of researchers' science tourism in promoting sustainable development within indigenous communities [32] , while Izurieta et al have demonstrated how scholars' engagement in science tourism has facilitated the achievement of Sustainable Development Goals, fostered community cohesion, and preserved cultural and ancestral values [33] . However, there are diverse opinions suggesting that science tourism can be categorized into visiting, listening to explanations, and hands-on participation ( [34] cited from Ereshko F. I., 2006). For instance, Räikkönen et al conducted a study on the motivations of tourists for natural science tourism in Seili Island, Finland revealed that the primary motivation behind science tourism is learning purposes [35] .…”
Section: Reviewmentioning
confidence: 99%
“…For instance, Buzinde et al advocate for the potential of researchers' science tourism in promoting sustainable development within indigenous communities [32] , while Izurieta et al have demonstrated how scholars' engagement in science tourism has facilitated the achievement of Sustainable Development Goals, fostered community cohesion, and preserved cultural and ancestral values [33] . However, there are diverse opinions suggesting that science tourism can be categorized into visiting, listening to explanations, and hands-on participation ( [34] cited from Ereshko F. I., 2006). For instance, Räikkönen et al conducted a study on the motivations of tourists for natural science tourism in Seili Island, Finland revealed that the primary motivation behind science tourism is learning purposes [35] .…”
Section: Reviewmentioning
confidence: 99%
“…Environmental and ethnographic factors play a key role in the development of northern tourism. The indigenous population has retained their traditional way of life, while the traditional management of natural resources is becoming the main factor in the development of northern entrepreneurship (Kamičaitytė-Virbašienė et al, 2018). The unique natural resources found in the Republic of Sakha (Yakutia), Russia, greatly contribute to the development of tourism, which, thus, can become an alternative economic activity and a source of income.…”
Section: Introductionmentioning
confidence: 99%